Analysis of education level in access and use of health care services, ISA-Capital, São Paulo, Brazil, 2003 and 2015 - Edige Felipe de Sousa Santos; Marília Cristina Prado Louvison; Elaine Cristina Tôrres Oliveira; Camila Nascimento Monteiro; Marilisa Berti de Azevedo Barros; Moisés Goldbaum; Chester Luiz Galvão Cesar (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
The great socioeconomic inequality that prevails in Brazil and the existence of a national health system with universal coverage places the need to monitor the evolution and social inequities regarding access to these services. This study aims to analyze the changes in the prevalence of health care use and the extent of social inequality in the demand, use and, access, resolution of health problems, satisfaction, and health care use of Brazilian Unified National Health System (SUS) according to education levels in the population living in the urban area of the Municipality of São Paulo, in 2003 and 2015. We analyzed data from two population-based household health surveys (Health Survey in São Paulo City - ISA-Capital) from 2003 and 2015. Dependent variables related to health care use in the two weeks preceding the survey and due to diseases included demand, access, satisfaction, problem resolution, and the public or private nature of the service. Prevalence was estimated using level of education and prevalence ratios (PR) by the Poisson regression. In the period, the demand for health care, access, resolution, and use of public health care increased from 2003 to 2015. Inequities in public health care use changed from 2003 to 2015 according to level of education. We found no social inequities in health care use in the municipality of São Paulo regarding demand, access, satisfaction, and resolution according to levels of education. Results show progress in the use and resolution of health care services, as well as the strong concentration of the use of SUS by the population with lower education. Results indicate the progress that SUS has made, but also show persistent challenges in the use and access to services.